2014
DOI: 10.1002/cbic.201402119
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Calicheamicin Orsellinate C2‐O‐Methyltransferase CalO6

Abstract: While bacterial iterative type I polyketide synthases (iPKSs) are now known to participate in the biosynthesis of a small set of diverse natural products, the subsequent downstream modification of the resulting polyketide products remains poorly understood. Toward this goal, we report functional characterization of the putative orsellinic acid C2-O-methyltransferase (CalO6) involved in calicheamicin biosynthesis. This study suggests C2-O-methylation precedes C3-hydroxylation/methylation and C5-iodination and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Genomic analysis, gene disruption, and structural characterization with ligands can suggest function for natural product biosynthetic enzymes (15,38,39), and our data strongly support a role for HygX in catalyzing orthoester linkage formation. Together, these data suggest a fully decorated three-ringed compound lacking the orthoester linkage as the substrate and narrows the possibilities for HygX substrates to two alternative anomers at C1 of the destomic acid moiety.…”
Section: Discussionsupporting
confidence: 61%
“…Genomic analysis, gene disruption, and structural characterization with ligands can suggest function for natural product biosynthetic enzymes (15,38,39), and our data strongly support a role for HygX in catalyzing orthoester linkage formation. Together, these data suggest a fully decorated three-ringed compound lacking the orthoester linkage as the substrate and narrows the possibilities for HygX substrates to two alternative anomers at C1 of the destomic acid moiety.…”
Section: Discussionsupporting
confidence: 61%
“…Cell disruption was achieved by sonication on ice in pH 8.8 reaction buffer (40 mM Tris HCl, 100 mM NaCl). Initial bioconversion experiments were carried out with the racemic mixture of substrate surrogates rac - 14d (0.25 mM), 5 mM MgCl 2 and 0.97 mM SAM tosylate for 16 h at 28 °C (Figure 1, for unprocessed spectra see Figures S48–S53) [26,27]. HPLC-MS analysis showed that rac - 14d was almost completely converted into the respective O -methylated product mixture rac - 15d (Figure 1f).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, CalO6 did not form suitable crystals in the presence of 1-2 mM SAM, SAH, or 2-5 mM substrate N -acetylcysteamine orsellinic acid (SNAC-OSA; used with or without SAH), nor did we observe these ligands in the electron density map upon soaking them into crystals of CalO6 grown in their absence. These ligand concentrations were several-fold higher than the previously reported K m values (0.3 mM for SAM and 1.3 mM for SNAC-OSA) [ 8 ], which ensured that most CalO6 is in a ligand-bound form at the conditions of the reported activity assays. However, we could not exclude a possibility that the ligand binding was disfavored in the crystallization solution.…”
Section: Methodsmentioning
confidence: 75%
“…Fractions containing pure CalO6 (as determined by SDS-PAGE), were pooled and the protein was concentrated to ~14 mg/mL in an Amicon Ultra-15 filtration unit and stored at 4 °C for use in crystallization experiments. The purified protein (Additional file 1 : Figure S1 in Supporting information) was assayed as reported previously [ 8 ] and exhibited similar activity in methylating S - N -acetylcysteaminyl orsellinic acid, as detected by HPLC. SeMet-substituted CalO6 was prepared as previously described [ 11 ] and purified analogously to the unsubstituted CalO6.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation